VALUE-AT-RISK AND EXPECTED SHORTFALL BASED ON PEAKS OVER THRESHOLD METHOD - CICILIA PEMBAYUN NOVIANSISTA CORNELIS , FRANSISKA
Extreme Value Theory has a role in the risk management of a data loss, that is one of way for modeling and measuring extreme risk of a data loss. In this Final Project, application of Extreme Value Theory focused on the Peaks Over Threshold method. This method is applied to a data which have extreme loss. The type of distribution which used on data loss is Generalized Pareto Distribution. Extreme risk of data loss which has applied the Extreme Value Theory will be measured using Value-at-Risk and Expected Shortfall. The measurement results show that the risk of data loss which apply Extreme Value Theory can reach extreme risk of the data, while data loss which do not apply Extreme Value Theory can not.